Loss of NLRP3 reduces oxidative stress and polarizes intratumor macrophages to attenuate immune attack on endometrial cancer - Zhu, Xiaolu; Xu, Yanli; Wang, Juan; Xue, Zhuowei; Qiu, Tian; Chen, Jing (Frontiers in Immunology, 2023)
Introduction The interaction between endometrial cancer (EMC) cells and intratumoral macrophages plays a significant role in the development of the disease. PYD domains-containing protein 3 (NLRP3) inflammasome formation triggers caspase-1/IL-1β signaling pathways and produces reactive oxygen species (ROS) in macrophages. However, the role of NLRP3-regulated ROS production in macrophage polarization and the subsequent growth and metastasis of EMC remains unknown. Methods We conducted bioinformatic analysis to compare NLRP3 levels in intratumoral macrophages from EMC and normal endometrium. In vitro experiments involved knocking out NLRP3 in macrophages to shift the polarization from an anti-inflammatory M1-like phenotype to a proinflammatory M2-like phenotype and reduce ROS production. The impact of NLRP3 depletion on the growth, invasion, and metastasis of co-cultured EMC cells was assessed. We also evaluated the effect of NLRP3 depletion in macrophages on the growth and metastasis of implanted EMC cells in mice. Results Our bioinformatic analysis showed significantly lower NLRP3 levels in intratumoral macrophages from EMC than those from normal endometrium. Knocking out NLRP3 in macrophages shifted their polarization to a proinflammatory M2-like phenotype and significantly reduced ROS production. NLRP3 depletion in M2-polarized macrophages increased the growth, invasion, and metastasis of co-cultured EMC cells. NLRP3 depletion in M1-polarized macrophages reduced phagocytic potential, which resulted in weakened immune defense against EMC. Additionally, NLRP3 depletion in macrophages significantly increased the growth and metastasis of implanted EMC cells in mice, likely due to compromised phagocytosis by macrophages and a reduction in cytotoxic CD8+ T cells. Discussion Our results suggest that NLRP3 plays a significant role in regulating macrophage polarization, oxidative stress, and immune response against EMC. NLRP3 depletion alters the polarization of intratumoral macrophages, leading to weakened immune defense against EMC cells. The reduction in ROS production by the loss of NLRP3 may have implications for the development of novel treatment strategies for EMC.